2014
DOI: 10.1155/2014/394206
|View full text |Cite
|
Sign up to set email alerts
|

TNF-αand Microalbuminuria in Patients with Type 2 Diabetes Mellitus

Abstract: Aim. Recent evidence suggests that chronic subclinical inflammation plays a key role in the pathogenesis and progression of diabetic nephropathy. Aim of the present study was to investigate possible correlation between the presence and degree of microalbuminuria and markers of inflammation in patients with type 2 diabetes mellitus (DM). Patients-Methods. Eighty patients were enrolled and clinical and laboratory data were recorded. Albumin-creatinine ratio (ACR) was calculated in first-morning urine samples. Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
44
2
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(57 citation statements)
references
References 36 publications
8
44
2
3
Order By: Relevance
“…These data are in agreement with Lampropolou et al [15] and Ruotsalainen et al [16]. In a previous study [17], we have also shown that inflammatory status is associated with nephropathy in DM1, since higher plasma levels of INF-c, TNF-a, IL-6, IL-10 in patients with diabetes and CKD (albuminuria C30 mg/g and/or GFR \60 mL/min/ 1.73 m 2 ) were observed when compared to those without CKD.…”
Section: Discussionsupporting
confidence: 94%
“…These data are in agreement with Lampropolou et al [15] and Ruotsalainen et al [16]. In a previous study [17], we have also shown that inflammatory status is associated with nephropathy in DM1, since higher plasma levels of INF-c, TNF-a, IL-6, IL-10 in patients with diabetes and CKD (albuminuria C30 mg/g and/or GFR \60 mL/min/ 1.73 m 2 ) were observed when compared to those without CKD.…”
Section: Discussionsupporting
confidence: 94%
“…On the contrary, there were non-significant correlation between serum and urinary TNF-α and serum creatinine or eGFR; similar results confirmed by Lampropoulou et al, (2014), they observed no correlation between eGFR and serum or urinary TNF-α [30].…”
Section: Similar To Our Results Molitch Et Al (2004)supporting
confidence: 82%
“…However, it should be noted that it remains unclear whether TNF-α urinary excretion is a marker of glomerular permeability or reflects tubulointerstitial damage [30]. Also Navarro et al, (1999) didn't find any significant correlation between serum and urinary concentrations and explained these results by an intra renal production of TNF-α [31].…”
Section: Similar To Our Results Molitch Et Al (2004)mentioning
confidence: 99%
See 1 more Smart Citation
“…This relationship has been found in other studies as well. (16)(17)(18)(19) However, not all studies have found this correlation between retinopathy and albuminuria. In the NHANES study, Kramer et al have found 30 % of patients with chronic renal insufficiency with neither retinopathy nor albuminuria; they did not find any correlation between retinopathy and albuminuria either.…”
Section: Discussionmentioning
confidence: 96%